Effect of graded posterior element and ligament removal on annulus stress and segmental stability in lumbar spine stenosis: a finite element analysis study - Lin, Maohua; Doulgeris, James; Dhar, Utpal Kanti; O’Corner, Timothy; Papanastassiou, Ioannis Dimitri; Tsai, Chi-Tay; Vrionis, Frank D. (Frontiers in Bioengineering and Biotechnology, 2023)
The study aimed to investigate the impact of posterior element and ligament removal on the maximum von Mises stress, and maximum shear stress of the eight-layer annulus for treating stenosis at the L3-L4 and L4-L5 levels in the lumbar spine. Previous studies have indicated that laminectomy alone can result in segmental instability unless fusion is performed. However, no direct correlations have been established regarding the impact of posterior and ligament removal. To address this gap, four models were developed: Model 1 represented the intact L2-L5 model, while model 2 involved a unilateral laminotomy involving the removal of a section of the L4 inferior lamina and 50% of the ligament flavum between L4 and L5. Model 3 consisted of a complete laminectomy, which included the removal of the spinous process and lamina of L4, as well as the relevant connecting ligaments between L3-L4 and L4-L5 (ligament flavum, interspinous ligament, supraspinous ligament). In the fourth model, a complete laminectomy with 50% facetectomy was conducted. This involved the same removals as in model 3, along with a 50% removal of the inferior/superior facets of L4 and a 50% removal of the facet capsular ligaments between L3-L4 and L4-L5. The results indicated a significant change in the range of motion (ROM) at the L3-L4 and L4-L5 levels during flexion and torque situations, but no significant change during extension and bending simulation. The ROM increased by 10% from model 1 and 2 to model 3, and by 20% to model 4 during flexion simulation. The maximum shear stress and maximum von-Mises stress of the annulus and nucleus at the L3-L4 levels exhibited the greatest increase during flexion. In all eight layers of the annulus, there was an observed increase in both the maximum shear stress and maximum von-Mises stress from model 1&2 to model 3 and model 4, with the highest rate of increase noted in layers 7&8. These findings suggest that graded posterior element and ligament removal have a notable impact on stress distribution and range of motion in the lumbar spine, particularly during flexion.